'Communication sovereignty' as resistance: strategies adopted by women farmers amid the agrarian crisis in India. Issue 1 (2nd January 2019) - Dutta, Mohan Jyoti; Thaker, Jagadish
ABSTRACT: This study draws on a culturally centered collaboration with a community of dalit women farmers in South India who were organized in a cooperative in their collective resistance against the corporatization of agriculture. Situated in the backdrop of the epidemic of farmer suicides in the region, this manuscript examines how those at the margins of global neoliberal transformations symbolically and materially make sense of and resist these transformations. The voices of the women farmers disrupt the underlying neoliberal assumptions that undergird the importation of cash crop agriculture into a subsistence and community-centered farming culture. They depict the ways in which Western cash crop agriculture disrupts community, food security, local health care systems, and the unique gender relations. Moreover, the communication advocacy work carried out by the women seeks to transform agricultural policy through material interventions as alternative practices of agriculture that challenge the hegemony of cash-based individualized agriculture.